Investigating Doxorubicin’s mechanism of action in cervical cancer: a convergence of transcriptomic and metabolomic perspectives - Huang, Zhuo; Jing, Huining; Lv, Juanjuan; Chen, Yan; Huang, YuanQiong; Sun, Shuwen (Frontiers in Genetics, 2023)
Cervical cancer remains a significant global health burden, and Doxorubicin is a crucial component of the therapeutic arsenal against this disease. However, the molecular mechanisms underpinning its therapeutic action remain incompletely understood. In this study, we adopted a multi-omics approach, integrating transcriptomic and metabolomic analyses with cellular and in vivo experiments to elucidate the molecular landscape associated with Doxorubicin treatment in cervical cancer. Our unbiased differential gene expression analysis revealed a stratification of gene expression alterations, with the ANKRD18B gene emerging as a notable player in response to Doxorubicin treatment. In parallel, our metabolomic analysis demonstrated significant perturbations in metabolite profiles, particularly L-Ornithine, suggesting a complex remodeling of metabolic pathways. Intriguingly, we uncovered a strong correlation between the gene ANKRD18B and the metabolite L-Ornithine, hinting at a tightly controlled gene-metabolite network. This correlation was further validated through rigorous cellular and in vivo experiments, which revealed a significant decrease in subcutaneous tumor size and significant alterations in the levels of ANKRD18B, L-Ornithine, and Doxorubicin concentration. Our findings highlight the intricate interplay between transcriptomic and metabolomic changes in response to Doxorubicin treatment, with potential implications for the design of improved therapeutic strategies for cervical cancer. The discovery of ANKRD18B and L-Ornithine as key players paves the way for future research aiming to unravel the complex molecular networks underlying the therapeutic mechanism of Doxorubicin. While our study lays a solid foundation, it also points towards the need for further exploration to fully understand these interactions and their implications for cervical cancer treatment.